Accurate prediction of maximum hydrogen sulfide absorption capacity in sour gas prewash units of natural gas treating plants. (1st February 2016) - ZareNezhad, Bahman; Khorramirad, Ramezan
ABSTRACT: A neuro-fuzzy model is proposed for accurate prediction of the maximum H2 S absorption capacity in aqueous phase over wide ranges of temperatures and salt concentrations. Predictions of the presented fuzzy model are much more accurate than those obtained through the available thermodynamic alternatives. The proposed neuro-fuzzy model can be used for accurate design of new prewash gas sweetening units at the upstream of amine sweetening plants in oil and gas industries.